Vascular plants of the UWM Field Station area - (:unkn) unknown (My University, 1990)
Since 1967, Field Station staff and volunteers have been assembling a vascular plant species list and herbarium for the Field Station. For the purpose of this list the Field Station area is defined as a 15.5 km2 (6 mi2) area that includes all of the Cedarburg Bog, the Sapa Spruce Bog and the uplands surrounding the Field Station and uplands immediately peripheral to the Bog. The vascular plant species list includes 681 taxa (species, varieties, forms, and named hybrids) in 97 families. 455 of these taxa, collected from the area, are contained in the Field Station herbarium. The list is undoubtedly incomplete, but is nevertheless useful to researchers, teachers and students. I hope that publishing and circulating the present list will encourage researchers to update the census and provide appropriate corrections.
Keywords: vascular plant list; UWM Field Station